Anti-TB Drug for Tuberculosis Spondylitis - Chandra Satria Ibrahim (Neurologico Spinale Medico Chirurgico, 2018)
Tuberculosis spondylitis, or spinal tuberculosis, is a disease that occurs throughout the world. Conservative therapy that is given to patients with spinal tuberculosis actually gives good results, but in certain cases, it requires surgery and rehabilitation therapy. The incidence of tuberculous spondylitis varies worldwide and is usually associated with the quality of available public health service facilities as well as the social factors in the country. Currently, tuberculosis spondylitis is a major source of morbidity and mortality in underdeveloped countries, especially in Asia, where malnutrition and population still remains a major issue. The goals of therapy in tuberculosis spondylitis are eradication of infection or at least to prevent neurological deterioration, and prevention or correction of a deformity or neurological deficit. Administration of anti-tuberculosis drugs is a major therapeutic principle in all cases including spinal tuberculosis. Early administration of anti-tuberculous drugs can significantly reduce morbidity and mortality.